A Descriptive Study To Assess The Knowledge And Practices Regarding Breastfeeding Among C-Section Mothers In Selected Hospital Of Abala, Haryana - Ms. Shikha Chaudhary; Ms. Geetanshi; Mr. Harsh (The Bioscan, 2026)
Background: Due to the dynamic and interactive nature of breastfeeding and the special living qualities of breastmilk, human infants (aged ≤12 months) and young children (aged 12-36 months) who receive human milk from their mothers through breastfeeding have the best chance of surviving, growing, and developing to the fullest extent possible. Breastfeeding lowers the risk of obesity and chronic diseases in later life and supports healthy brain development.